'So far so good': Academic migrants adjust to teaching in Aotearoa New Zealand's tertiary vocational sector - Maggie Masterson; Frances Edwards (New Zealand Journal of Teachers' Work)
Tertiary education providers increasingly recruit international teaching staff in their drive to fill skills gaps and build institutional knowledge and research capacity but literature examining the adjustment experiences of these academic migrants remains limited.  This multiple case study focuses on Aotearoa New Zealand’s ITP (Institutes of Technology and Polytechnics) sector and explores how the experience of migration has impacted on four long-term academic staff with a range of industry, teaching and research experience.